2023
DOI: 10.3389/fvets.2023.1123002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Chinese yam polysaccharide copper complex on growth performance, immunity, and antioxidant capacity of broilers

Abstract: Chinese yam polysaccharide (CYP) has received attention in recent years owing to its positive nutritional and medicinal characteristics. Copper is an essential trace metal in animals, which plays an important role in iron absorption and hemoglobin synthesis. However, no published study has evaluated Chinese yam polysaccharide copper complex (CYP-Cu) as a dietary additive in broilers. This study was conducted to investigate the effects of dietary CYP-Cu on growth performance, immunity, and oxidative resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In recent years, increasing numbers of studies have shown that polysaccharide metal complexes display diverse biological activities, such as improving growth, antioxidation, immune regulation, and antibacterial activity. Zhang et al ( Zhang J et al, 2023 ) reported that the supplementation of dietary Chinese yam polysaccharide-Cu complex could improve the indexes of the growth, carcass, serum biochemistry, immunity and oxidation resistance in broilers, such as average daily gain, the slaughter percentage, breast muscle percentage, leg muscle percentage, growth-related hormones insulin-like growth factor I, triiodothyronine, thyroxine, growth hormone, insulin, antibodies and the cytokines, IgM, IgG, IgA, IL-2, IL-4, IL-6, T-SOD, T-AOC, GSH-Px, and GSH-ST. Research showed that soybean polysaccharide iron complex can promote the growth of the beneficial bacteria Bacillus licheniformisand inhibit the proliferation of the pathogenic bacteria Staphylococcus aureus , thus improving the growth and immunity of the body ( Gao W et al, 2020 ). Due to their safety, growth-promoting effect, and immune-enhancing properties are used as functional feed additives in animal production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, increasing numbers of studies have shown that polysaccharide metal complexes display diverse biological activities, such as improving growth, antioxidation, immune regulation, and antibacterial activity. Zhang et al ( Zhang J et al, 2023 ) reported that the supplementation of dietary Chinese yam polysaccharide-Cu complex could improve the indexes of the growth, carcass, serum biochemistry, immunity and oxidation resistance in broilers, such as average daily gain, the slaughter percentage, breast muscle percentage, leg muscle percentage, growth-related hormones insulin-like growth factor I, triiodothyronine, thyroxine, growth hormone, insulin, antibodies and the cytokines, IgM, IgG, IgA, IL-2, IL-4, IL-6, T-SOD, T-AOC, GSH-Px, and GSH-ST. Research showed that soybean polysaccharide iron complex can promote the growth of the beneficial bacteria Bacillus licheniformisand inhibit the proliferation of the pathogenic bacteria Staphylococcus aureus , thus improving the growth and immunity of the body ( Gao W et al, 2020 ). Due to their safety, growth-promoting effect, and immune-enhancing properties are used as functional feed additives in animal production.…”
Section: Discussionmentioning
confidence: 99%
“…As a complex carbohydrate, polysaccharide has the ability to chelate metal ions, thereby improving the bioavailability of metal ions and helping to maintain the normal physiological function of the body. Notably, polysaccharide-Cu 2+ chelates have demonstrated the potential to improve animal growth performance and exhibit significant intestinal immune-boosting functions ( Zhang J et al, 2023 ). Various studies have highlighted the antioxidant and multifunctional iron supplement potential of polysaccharide metal chelates, including dioscorea polysaccharide iron chelate (DTP-Fe), which can enhance the scavenging of DPPH free radicals ( Liu Y et al, 2023 ), ABTS+ and hydroxyl free radicals in the organism, with the antioxidant capacity of TDP-Fe increasing with higher concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the high amino acid digestibility of the CPC diet, which improved the overall development of broilers and consequently enhanced their antioxidant capacity. In addition, IgA, IgG, and IgM are considered important parameters reflecting the humoral immune status of animals [32,33]. The level of serum immunoglobulin to a certain extent reflects the immune function of animals, which helps to alleviate immune stress, improve health status, and improve growth performance [34].…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of dietary Chinese yam polysaccharide-Cu (0.10 g/kg) improved the growth, immunity, and oxidation resistance of broilers ( 28 ). Excess Cu induces hepatic cholesterol metabolism dysfunction, and the miR-455-3p-OXSR1 axis works as a regulator of autophagy under Cu stress ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%